Analysing the impact of smart city service quality on citizen engagement in a public emergency. (January 2022) - Zhu, Wenlong; Yan, Ruzhen; Song, Ying
Abstract: The outbreak of novel coronavirus disease 2019 (COVID-19) has brought great challenges to the improvement of global smart city services. To date, few studies have been conducted on the effects of service quality on citizen engagement in smart cities in a public emergency. Based on the stimulus-organism-response (SOR) model and uncertain management theory, this study analyses the impact of the service quality of smart city system on citizen engagement in a public emergency. Data were collected in Chinese smart cities. Three valuable and novel results are identified. First, high-quality information content, highly reliable systems and highly responsive systems have a significant positive effect on citizens' continuous experiences, but not on citizens' immediate experiences. Second, both the immediate and continuous experiences of citizens have a significant positive effect on citizen engagement. Third, continuous experiences impose a full mediation effect between information content and citizen engagement, between reliability and citizen engagement and between responsiveness and citizen engagement. As its main contribution, this study focuses on the construction of a theoretical model. Based on this model, smart city managers can understand citizens' reactions in public emergencies from stimulation to experience and their behaviours in relation to smart city services. Highlights: This study constructs a model to analyse citizen engagement in a public emergency. Service quality has a significant positive impact on continuous experiences. Flow experiences have a significant positive influence on citizen engagement. Continuous experiences mediate the effect of service quality on citizen engagement.